Human Resource Development Strategy And Multimodal Transportation Performance: The Mediating Role Of Digital Competence In Ferry Transportation Services - Surnata Surnata; Eko Nugroho Widjatmoko; Rispa Saeful Mu’tamar; Febriansyah (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2026)
This study examines the effect of Human Resource Development (HRD) strategies on multimodal transportation performance in the Tanjung Api-Api ferry transportation sector, with employees’ digital competence acting as a mediating variable. The study contributes to the literature by proposing and empirically validating an integrated model linking HRD strategy, digital competence, and multimodal transportation performance in the ferry transportation sector, a context that has received limited empirical investigation. A quantitative approach with an explanatory research design was employed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected from 185 operational employees and multimodal transportation service personnel. The findings reveal that HRD strategies positively and significantly influence both employees’ digital competence and multimodal transportation performance. Employees’ digital competence also significantly enhances service efficiency, operational productivity, service quality, and intermodal coordination. Furthermore, digital competence significantly mediates the relationship between HRD strategies and transportation performance. The coefficient of determination (R²) value of 0.742 indicates that the model has strong predictive power. These findings extend existing knowledge by demonstrating the critical role of digital competence as a mechanism through which HRD strategies improve transportation performance. Practically, the results provide guidance for transportation operators and policymakers in designing digital competency-based HRD programs to support the effectiveness, efficiency, and sustainability of multimodal transportation systems in the era of digital transformation.